Pemimpin - Asip E. Hadipranata (Unisia, 2004)
Basically, for who believe in the saying of the Prophet, everyone is a leader who must be accountable to others. Part of requirements for a good leader is well knowing about abstract and real things, means having a capability for predicting the future together fith imtaq (believing in God and doing all his commands), and the other requirement is that leader must be well mastering science and technology which is realistic and operational, and therefore, he can set up a good action planning based on tyhose tywo needed requirements.